La percepción ambiental de las actividades de extracción minera: parroquia La Paz del cantón Yacuambi. - Ayala Camacho, Gabriela Krupskaya (2014)
This research shows environmental perception that the inhabitants of the parish of La Paz have developed toward mining activities. It is described the mining situation in Latin America, Ecuador and in the province of Zamora Chinchipe. It also includes positive and negative aspects of mining is included, performing a general approach on the different theories of environmental perception. The general scientific method is applied, along with the inductive and deductive method. A sample was randomly applied; the results were treated in a cross-sectional descriptive study using responses recorded in surveys and interviews with representative leaders. The method of K-Means was used to obtain four clusters in which low, medium and high environmental perception was determined. Finally, it is evident that in the parish of La Paz, the practice of small-scale and artisanal mining is done without adequate health and safety measures or environmental control. Is the biocultural process that determines the environmental perception of the inhabitants of the parish of La Paz and in a lesser degree influences the level of education acquired.